Terapi Doa Dalam Pelayanan Pembinaan Spiritual Islam Untuk Mengurangi Tingkat Kecemasan Pasien Persalinan di Rumah Sakit - Silma Mumtahanah; Novia Fetri Aliza (Al-Ittizaan: Jurnal Bimbingan Konseling Islam, 2022)
The process of childbirth is a condition that is awaited by a husband and wife to be able to meet the baby. However, a feeling of anxiety often comes to every couple, especially pregnant women who are going through the labor process so that this can interfere with the mental health of pregnant women. This study aims to describe the process, effectiveness, importance of the application of prayer therapy as well as the supporting and inhibiting factors of the application of prayer therapy in Islamic Spiritual Development services, in reducing the anxiety level of delivery patients at the hospital. The research was conducted using qualitative methods. This type of research is field research (field research). There were six subjects in this study, namely three Islamic Ruhani Bina officers and three labor patients. Data were analyzed through editing, data coding and data interpretation. The results showed that the application of prayer therapy was carried out by meeting the patient, conducting an assessment to determine the level of anxiety with an interpersonal communication approach and then intervening by looking at the level of anxiety felt by the patient. In addition, this study also proved that spiritual assistance is given in the form of prayer, namely by reminding patients to make more istighfar, reading prayers or short surahs in the Qur'an which the patient memorizes and reads repeatedly because specifically there is no prayer for giving birth. Based on qualitative analysis, the application of prayer therapy can reduce the anxiety level of labor patients. It can be seen by the expression that the patient is calmer and feels better than before.